Geological and hydrogeological concepts in the interpretation of electrical sounding: an example from Xiakou Landslide, Yaan City area, Sichuan, China - Pant, Surendra Raj; Wagner, A.; Li, T.; Yi, Fu Wei (Journal of Nepal Geological Society, 2002)
Due to unfavorable geological and hydrogeological condition the electrical resistivity data interpretation even from a small area such as a landslide can be affected. However, good results can be achieved by using geological and hydrogeological concept during modeling. The outputs of this work are based on the concepts prepared during qualitative analysis. After the modeling of the sounding curves by using geological and hydrogeological concepts the results were found surprisingly good than the results without concepts. Furthermore, there is a comparison between the vertical electrical sounding (VES) modeling results and drillhole information. It shows that VES modeling results provide better assessment of the rock mass in the subsurface than the drill core interpretation only.